Ice Marks in Newfoundland: A History of Ideas - Brookes, Ian (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1982)
ABSTRACTThis essay traces the evolution of ideas on the origin of features in Newfoundland now ascribed to glaciation, through the period 1822-1981. It identifies "Pre-cognitive," "Drift," and "Glacial" phases, with the last phase divided into seven sub-phases. In the Glacial Phase, debate centred on 1) the relative roles of Labrador ice and ice from the island of Newfoundland, 2) the areal and vertical extent of ice masses, and 3) the number and chronology of glacial episodes. Alexander Murray is credited with first recognizing glaciation in Newfoundland in 1866, and the background to his perspicacity is discussed. The evolution of ideas from the late-nineteenth century to the present is related to improving access, exploration by increasingly widely experienced scientists, the import of concepts from outside the region, the development of chronological tools, and improvements in glaciological theory.